Socio-demographic characteristics of students as a predictor of their attitude towards elderly people - Bar, Zoran; Adamović, Milosav V; Stosljevic, Miodrag (Sociološki pregled, 2025)
The main goal of the paper is to examine the differences in the expression of positive and negative attitudes towards the general population of elderly people in relation to the respondents’ gender, age and level of education. The research was conducted on a sample of 321 respondents, the students of social sciences and humanities in the territory of Belgrade, Novi Sad, Niš, Kragujevac and Jagodina, in the period from November 2019 to February 2020. The Kogan’s Attitude towards Old People scale was used for data collection. The results indicated the existence of statistically significant differences in the respondents’ responses in relation to age (p < 0,004; p < 0,000) and level of education (p < 0,001; p < 0,002), as well as a greater expression of positive versus negative attitudes (p < 0,000). The pronounced presence of attitudes towards older people changes with the respondents’ age and in relation to their level of education.
Keywords: socio-demographic differences; elderly people; attitudes